2015
DOI: 10.1001/jamaoto.2015.0791
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of PF-04958242 in Age-Related Sensorineural Hearing Loss

Abstract: clinicaltrials.gov Identifier: NCT01518920.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The results of these early trials, even if unsuccessful at identifying an efficacious therapy, will be important in informing the design of future ARHL clinical trials. The first reported clinical trial designed to treat ARHL with a pharmacological agent was conducted by Pfizer and completed in 2013 using PF-04958242, a positive allosteric modulator of the AMPA receptor, an ionotropic glutamate receptor (Bednar et al 2015).…”
Section: Therapeutic Approaches To Treating or Preventing Arhlmentioning
confidence: 99%
“…The results of these early trials, even if unsuccessful at identifying an efficacious therapy, will be important in informing the design of future ARHL clinical trials. The first reported clinical trial designed to treat ARHL with a pharmacological agent was conducted by Pfizer and completed in 2013 using PF-04958242, a positive allosteric modulator of the AMPA receptor, an ionotropic glutamate receptor (Bednar et al 2015).…”
Section: Therapeutic Approaches To Treating or Preventing Arhlmentioning
confidence: 99%
“…A recent clinical trial demonstrated that AMPA receptor potentiator (PF-04958242) attenuated the schizophrenia-relevant ketamine-induced cognitive impairment in verbal learning and working memory 100 , suggesting the use of AMPA receptor potentiator for the treatment of cognitive impairments associated with schizophrenia. Additionally, PF-04958242 has been shown to improve auditory function significantly in age-related sensorineural hearing loss 101 . Another AMPA receptor potentiator, LY451395, which has been in Phase II development with possible use in Alzheimer’s disease whereas abnormalities of glutamatergic homeostasis also occur.…”
Section: Discussionmentioning
confidence: 99%
“…The substantial prolongation of the cerebellar synaptic currents by both PAMs is consistent with the known motor side effects of high-impact PAMs at higher exposures (Zasadny et al, 2009;Shaffer et al, 2013Shaffer et al, , 2015 and could potentially precipitate Purkinje cell toxicity that occurs when AMPARs are overactivated (Garthwaite and Garthwaite, 1991;Brorson et al, 1995). Though BIIB104 exhibits a clear cross-species, dose-dependent engagement of cerebellar processes (i.e., increased cGMP, motor dysfunction, and FDG uptake), no evidence of Purkinje cell toxicity has been reported (Shaffer et al, 2015), and the drug has been safe and welltolerated in humans (Zasadny et al, 2009;Bednar et al, 2015). Procognitive activity occurs at nanomolar free drug concentrations (Shaffer et al, 2015;Ranganathan et al, 2017), with a projected therapeutic index of ∼37 for self-limiting tremors in humans (Shaffer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%